2019
DOI: 10.1016/j.foodchem.2019.01.161
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant ability of tyrosol and derivative-compounds in the presence of O2(1Δg)-species. Studies of synergistic antioxidant effect with commercial antioxidants

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Antioxidant ability of Tyrosol and derivative-compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Such protection can be from vitamin C, carotenoid, polyphenol, and flavonoids (Ahmadinejad et al 2017). Phenols contained in bacterial crude extract and flavonoids work as antioxidants by deactivating single protein species through physical and synergetic effects (Casadey et al 2019). Therefore, these compounds are able to increase the resistance level of S. pombe and eventually its growth.…”
Section: Discussionmentioning
confidence: 99%
“…Such protection can be from vitamin C, carotenoid, polyphenol, and flavonoids (Ahmadinejad et al 2017). Phenols contained in bacterial crude extract and flavonoids work as antioxidants by deactivating single protein species through physical and synergetic effects (Casadey et al 2019). Therefore, these compounds are able to increase the resistance level of S. pombe and eventually its growth.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic activity of antioxidants has been used in different areas, for example, in the food industry, the combination of antioxidants is studied to find a mixture that allows greater efficiency in food preservation, as well as a decrease in the number of synthetic additives [24][25][26][27]. In the pharmaceutical industry it has been found that the use of a mixture of antioxidants with some drugs increases therapeutic efficacy and decreases cell damage [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%